Breakage and displacement of the high-speed hand-piece bur during impacted mandibular third molar extraction: three cases - Kuncai Li; Bingqing Xie; Junliang Chen; Yun He (BMC, 2022)
Abstract Background The high-speed hand-piece bur is one of the methods to perform tooth sectioning during the minimally traumatic extraction of impacted mandibular third molars. During tooth sectioning, the breakage of the bur might take place when it is improperly used. Three cases of the breakage and displacement of a high-speed hand-piece bur during extraction are reported, aiming to remind dental surgeons of this complication. Case presentation The bur fragment in case 1 was embedded in the mandibular bone under the previously removed crown of tooth 48 and distal to tooth 47. The bur fragment in case 2 was embedded in the lingual edge of the socket and partly beneath the mucosa on the lingual side. The position of the bur fragment in case 3 was similar to that of case 1 but was completely embedded in the spongious bone. The three cases were performed by first-year residents, and all of the bur fragments were successfully removed by attending doctors after accurately locating them by radiological examination. Conclusions In order to avoid breakage of the high-speed hand-piece bur, the number of uses of the bur should be monitored and the integrity and state of the bur should be carefully checked. Moreover, light pressure with little lateral force should be used during tooth sectioning. If bur breakage and displacement occur, the retrieval protocol should be determined based on the imaging findings and conducted as soon as possible to avoid serious consequences.